The Zakat Payment Behavior of Muslim Merchants in Sungai Penuh City - Sarmigi, Elex; Azhar, Azhar (Prodi Manajemen Zakat dan Wakaf Fakultas Ekonomi dan Bisnis Islam, 2025)
This study aims to understand the zakat payment behavior of Muslim traders in Sungai Penuh City. The method used is a qualitative approach with a phenomenological study to explore the experiences and meanings of the traders regarding zakat. Data were collected through in-depth interviews, participatory observation, and documentation. Data analysis employed the Miles and Huberman model, using data reduction, data presentation, and conclusion drawing techniques. The results show that zakat payment behavior is influenced by factors such as religious understanding, economic status, and trust in zakat management institutions. This study is expected to contribute to increasing traders' awareness and compliance in fulfilling their zakat obligations.